Pengembangan Video Pembelajaran Matematika berbasis Realistic Mathematics Education pada Pembelajaran Segiempat - Ayu, Andi Nur Egidia Fahmi; Angriani, Andi Dian; Latuconsina, Nur Khalisah; Kusumayanti, Andi (Faculty of Tarbiyah and Teacher Training, 2024)
This study discusses the development of a mathematics learning video based on Realistic Mathematics Education (RME) on quadrilaterals, which aims to determine the process of developing a valid, practical, and effective RME-based mathematics learning video. The type of research used is research and development (R&D) with a 4D development model consisting of four stages: define, design, develop, and disseminate. The subjects of this study were 20 students of grade VII of SMP Negeri 4 Selayar. The instruments used included expert validation sheets, student activity observation sheets, teacher ability observation sheets in managing learning, student response questionnaires, teacher response questionnaires, and learning outcome tests. The developed learning video was declared valid based on the study's results. This video was declared practical based on the teacher's ability to manage learning, which was categorized as very good, and the results of the teacher response questionnaire were categorized as very practical. In addition, this video was also declared effective because it met three criteria for effectiveness: student response questionnaires with a very positive category, student activities that were classified as good, and mathematics learning outcome tests that achieved a 100% completion percentage. The development of RME-based learning videos provides valid, practical, and effective learning media, which can help teachers manage mathematics learning in a more interactive and meaningful way.